KOMUNIKASI EFEKTIF DAN KEPUASAN KERJA KARYAWAN (STUDY KASUS PT. XYZ) - Ridwan Ridwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
communications made by the man made ​​to relate to each other both in everyday life and at work. The importance of communication for humans can not be denied as well as for an organization or company. Employees generally have a fear to express her true feelings. The existence of poor communications cause harm for example in a restaurant. The first financial loss.